A method for separating and recycling a perovskite solar cell assembly based on laser processing

By employing laser etching and acid solution leaching, the challenges in the separation and recycling of perovskite solar cell modules have been solved, achieving efficient separation and recovery of valuable elements, reducing environmental pollution and energy consumption, and increasing the reuse value of materials.

CN121198719BActive Publication Date: 2026-11-06HUAZHONG UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511423157.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-30
Publication Date
2026-11-06
Estimated Expiration
2045-09-30

AI Technical Summary

Technical Problem

Existing technologies are difficult to efficiently separate and recover valuable elements in perovskite solar cell modules, and pose environmental pollution risks, especially the material damage and pollution caused by the use of toxic and harmful solvents and high-temperature processing.

Method used

Laser etching technology is used to separate the double-glass sandwich structure of perovskite solar cell modules, combined with acid solution leaching treatment, to recover valuable elements in the perovskite layer, avoiding the use of high temperature and organic solvents.

Benefits of technology

This technology enables efficient separation and recovery of valuable elements in perovskite solar cell modules, reducing energy consumption and environmental pollution risks, and improving recycling efficiency and the reuse value of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121198719B_ABST
    Figure CN121198719B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of waste perovskite battery recycling, and discloses a separation and recycling method of perovskite solar cell assembly based on laser processing, comprising the following steps: (1) mechanically disassembling the waste perovskite solar cell to obtain a double-layer glass sandwich structure; (2) focusing laser spots on the perovskite light-absorbing layer and / or carrier transport layer, and etching by using a pulsed laser beam to obtain two completely separated glass assemblies; by adjusting the frequency, output power and wavelength of the pulsed laser beam, the total residual load of the B-site elements of the perovskite material ABX3 meets the preset requirements; (3) performing acid leaching treatment to leach and recover valuable metal elements. By using the laser etching technology, the present application realizes the separation of the perovskite battery glass plate assembly, and cooperates with the subsequent acid solution leaching treatment to realize the recycling of the B-site elements of the perovskite material ABX3 and other valuable elements, and can completely retain two glass plates, which is beneficial to subsequent recycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of waste perovskite battery recycling technology, and more specifically, relates to a method for separating and recycling perovskite solar cell modules based on laser processing. Background Technology

[0002] With the rapid development of photovoltaic technology, the accumulation of waste photovoltaic modules has become increasingly prominent, creating an urgent need for efficient recycling and management of photovoltaic waste. Recycling waste photovoltaic modules to extract valuable raw materials and reusing them in the production of new modules not only reduces resource waste but also significantly improves economic feasibility, making it a solution that combines economic and ecological benefits.

[0003] Existing photovoltaic modules are mainly based on silicon solar cells. The external components such as aluminum alloy frames, waterproof junction boxes, EVA, and glass panels are similar to those of perovskite solar cells. The core difference lies in the internal structure. The key internal component of silicon solar cells is the electrode that connects P-type silicon and N-type silicon, while the key internal component of perovskite solar cells is the stacked structure of perovskite light-absorbing layer and carrier transport layer (such as hole transport layer and electron transport layer).

[0004] The photovoltaic module frame is disassembled and separated using methods such as single-sided, opposite-sided, and diagonal disassembly. Then, the glass panels of the photovoltaic module are disassembled and separated through whole-panel pyrolysis, chemical treatment by immersion in organic solvents, and mechanical crushing. The temperature of whole-panel pyrolysis is generally between 200-650 ℃, which may damage the module components; mechanical crushing faces difficulties in component sorting; and the chemical treatment reagents using organic solvents are highly toxic and may cause environmental pollution.

[0005] Perovskite solar photovoltaic (PV) modules, as an emerging photovoltaic technology, have shown the potential for rapid market expansion, providing sustainable clean energy at a lower cost. The structure of a perovskite solar PV module consists of glass, a perovskite light-absorbing / transmitting layer, an encapsulating film layer, and metal electrodes. To prevent the perovskite light-absorbing layer from contacting moisture in the air, the solar cell glass panel uses a polyolefin elastomer (POE) and a polyethylene-vinyl acetate copolymer (EVA) as an encapsulating film layer during manufacturing. This tightly bonds the film to seal the perovskite light-absorbing / transmitting layer and ensures environmental durability (the presence of the encapsulating film layer also prevents the cells from being directly immersed in acid).

[0006] However, separating the tightly packed solar cell glass panels from waste photovoltaic modules remains a technological challenge. Referring to the separation process for silicon-based solar cells, existing separation technologies for perovskite solar cells mainly include whole-panel pyrolysis, chemical treatment by immersion in organic solvents, and mechanical crushing. Although these technologies have made progress in material separation and recycling, each still has its shortcomings.

[0007] Patent CN114798680A discloses a method for recycling lead halide perovskite solar cells, including heat treatment to separate and remove the cover plate, and directly peeling off the metal electrode layer. This method involves subjecting the entire panel to thermal stress at 250°C for 2 minutes, causing the polymer sealant (epoxy resin) to melt and delaminate the lead halide perovskite solar module. However, the heat separation method inevitably generates volatile organic pollutants, causing secondary pollution.

[0008] Patent CN111438161A discloses a method for separating photovoltaic modules using a chemical solvent method. This method involves pulverizing the photovoltaic cell laminate, including the cover plate, into particles, adding them to an organic solvent, ultrasonicating and stirring to obtain an upper floating layer containing the backsheet, a water-soluble substance containing EVA adhesive, and a bottom precipitate containing glass and solar cells, thus completing the separation. The organic solvent used in this method is a non-polar solvent, including one or more of toluene, benzene, cyclohexane, chloroform, or dichlorobenzene. The reagents used in this method are all toxic and harmful organic solvents, posing risks to operators and the environment. Once the solar cell glass backsheet is broken, the possibility of direct cascade utilization is completely lost.

[0009] Patent CN111957723B discloses a method for recycling broken glass photovoltaic modules. The method involves crushing the broken glass photovoltaic modules (after removing the junction box, metal frame, and backsheet) into a granular mixture; heating the granular mixture to vaporize EVA material, causing the silicon wafers, glass, and metal solder ribbons to separate; sieving the separated silicon wafers, glass, and metal solder ribbons to separate the metal solder ribbons; and separating the silicon wafers and glass particles separately from the mixture containing the separated metal solder ribbons. However, this method uses mechanical crushing, which cannot completely separate the photovoltaic modules. The various materials are mixed together, resulting in low purity, requiring further pyrolysis or chemical treatment depending on the composition of the different components. Furthermore, once the solar cell glass backsheet is broken, the possibility of direct cascade utilization is completely lost.

[0010] Currently, chemical solvent recovery methods primarily rely on toxic and hazardous solvents, posing risks to the environment and operators. Laser cleaning for recovery cannot expose critical components like solar cell chips, requiring subsequent thermal treatment. Therefore, there is a need to develop a separation and recovery method for perovskite solar cell modules that ensures effective separation and recovery of valuable elements (such as lead in lead-based perovskites, tin in tin-based perovskites, and metallic elements in conductive materials) while minimizing pollution. Summary of the Invention

[0011] To address the aforementioned deficiencies or improvement needs of existing technologies, the present invention aims to provide a method for separating and recycling perovskite solar cell modules based on laser processing. Through laser etching technology, the perovskite solar cell glass panel module is separated. Combined with subsequent acid leaching, valuable elements such as B-site elements (e.g., lead and tin) in the perovskite material ABX3 layer are recovered, while both glass panels are preserved intact, facilitating subsequent reuse. This invention achieves highly efficient separation of waste perovskite solar cell modules, effectively solving the problem of inefficient disassembly and separation of glass panels in the existing perovskite solar cell recycling field.

[0012] To achieve the above objectives, the present invention provides a method for separating and recycling perovskite solar cell modules based on laser processing, characterized by comprising the following steps: (1) The frame and junction box of the waste perovskite solar cell are removed by mechanical disassembly to obtain a tightly bonded double-layer glass sandwich structure; the double-layer glass sandwich structure includes two glass plates and a sandwich layer between the two glass plates; (2) Focus the laser beam fully on the hole transport layer, perovskite light-absorbing layer and / or electron transport layer in the double-layer glass sandwich structure obtained in step (1), and use a pulsed laser beam to irradiate and etch the double-layer glass sandwich structure from the vertical glass surface through a full scan, so that the area scanned by the laser focus undergoes a change in properties and loses its adhesion ability, resulting in two completely separated glass plate assemblies, thus exposing the inner sandwich layer; by adjusting the frequency, output power and wavelength of the pulsed laser beam, the total remaining load of the B site element of the perovskite material ABX3 in the perovskite light-absorbing layer on the two completely separated glass plate assemblies meets the preset requirements; the preset requirements are that the total remaining load accounts for more than 90% of the original load, and the original load is the actual load of the B site element of the perovskite material ABX3 in the double-layer glass sandwich structure obtained in step (1); (3) The two complete and separated glass components obtained in step (2) are subjected to acid solution leaching treatment so that the adhering substances on each glass are completely dissolved in the leaching solution. Then, the valuable metal elements in the leaching solution after treatment are leached and recovered. The valuable metal elements include the B-site elements of the perovskite material ABX3 in the perovskite light-absorbing layer.

[0013] As a further preferred embodiment of the present invention, the valuable metal element also originates from the electron transport layer; The pulsed laser beam used in step (2) also satisfies that the ratio of the total remaining load of the metal elements in the electron transport layer on the two completely separated glass components to the original load of the metal elements in the electron transport layer in the double-layer glass sandwich structure obtained in step (1) is more than 90%.

[0014] As a further preferred embodiment of the present invention, the valuable metal element includes at least one of lead and tin; preferably lead.

[0015] As a further preferred embodiment of the present invention, in step (2), from the laser incident direction, the sandwich layer sequentially includes a hole transport layer, a perovskite light-absorbing layer, an electron transport layer, a conductive material layer and an encapsulation film layer, or sequentially includes an electron transport layer, a perovskite light-absorbing layer, a hole transport layer, a conductive material layer and an encapsulation film layer.

[0016] As a further preferred embodiment of the present invention, the conductive material layer is either FTO or ITO.

[0017] As a further preferred embodiment of the present invention, the encapsulating film layer is one of polyolefin elastomer (POE) and polyethylene-polyvinyl acetate copolymer (EVA).

[0018] As a further preferred embodiment of the present invention, in step (2), the frequency control range of the pulsed laser beam is 10-100KHz, the output power control range is 5-20W, and the wavelength control range is 355-1064nm; the processing speed of the pulsed laser beam is 0.5-5m / s; the full scanning method includes one of unidirectional scanning, bidirectional filling, and ring filling.

[0019] As a further preferred embodiment of the present invention, in step (2), the wavelength of the pulsed laser beam is one of 355nm, 532nm and 1064nm.

[0020] As a further preferred embodiment of the present invention, in step (3), the acid solution is one or more of nitric acid solution, hydrochloric acid solution, acetic acid solution and sulfuric acid solution.

[0021] Compared with the prior art, the above-described technical solutions conceived in this invention can achieve the following beneficial effects: (1) This invention proposes a method for separating perovskite components by laser etching, which solves the problem of difficulty in separating the double-layer glass (i.e., tightly bonded double-layer glass sandwich structure) in the first step of the waste component recycling process. The method of this invention can separate the tightly bonded double-layer glass sandwich structure by laser etching, exposing the light-absorbing layer, functional transmission layer, electrode and encapsulation film layer inside. It does not require heating the whole board, which greatly reduces the energy consumption of the process and improves the economic efficiency of the process.

[0022] For discarded perovskite solar cells, mechanical disassembly can remove the frame and junction box, resulting in a tightly bonded double-layered glass sandwich structure. This double-layered glass sandwich structure has a fully covered encapsulating film layer (i.e., an encapsulating film layer laid along the entire surface of the glass), making separation difficult. Physical separation would result in the glass breaking into irregular small pieces, losing its recycling value. This invention utilizes pulsed laser etching, focusing the laser beam comprehensively on the hole transport layer, perovskite light-absorbing layer, and / or electron transport layer within the resulting double-layered glass sandwich structure. The pulsed laser beam is incident perpendicular to the glass surface (i.e., the normal direction of the cutting surface in this invention is consistent with the laser incident direction) for one (or more) laser surface scans, which can break the adhesion, achieving separation and exposing the internal sandwich layer, thus obtaining two completely separated glass components (the glass will not break). The entire process does not require chemical treatment of the encapsulating film layer using desiccant or similar chemicals. Furthermore, the two completely separated glass components can be directly processed by acid leaching to extract the target valuable elements, without the need for organic solvents such as DMF or additional heat treatment.

[0023] (2) The pulsed laser used in the laser etching of this invention has a wavelength of 355-1064nm, a power of 5-20W, and a repetition frequency of 10-100KHz, which can effectively control the generation of smoke and odor and reduce environmental hazards.

[0024] This invention utilizes pulsed lasers, where the laser source can concentrate energy onto the focal plane within a nanosecond timescale. Due to the extremely short pulse duration, thermal diffusion effects are effectively suppressed, resulting in a localized, instantaneous temperature surge (of course, laser power needs to be controlled to avoid excessively high temperatures, which would hinder the recycling of valuable metal components from discarded perovskite solar cells). This rapid, localized temperature surge triggers non-equilibrium physical processes on the focal plane (e.g., ionization, melting, and vaporization), improving dismantling efficiency and reducing the risk of damage to the material structure. Since the total thickness of the perovskite light-absorbing layer and transport layer (including the hole transport layer, perovskite light-absorbing layer, and electron transport layer) in a perovskite solar cell is much smaller than that of the encapsulating film layer, this invention only requires focusing the laser onto the perovskite light-absorbing layer and / or the carrier transport layer. This invention scans the entire surface of the glass with the laser perpendicular to the glass, ensuring that all light spots pass through the first glass layer (the laser can pass through the first glass layer but not the perovskite layer).

[0025] (3) This invention achieves the separation of perovskite solar cell glass plate components through laser etching. The selection of laser power and frequency affects the etching effect of the components. When the laser power is too high and the frequency is too low, it may cause excessive material volatilization or instantaneous melting and rapid solidification of the encapsulating film layer, thereby affecting the processing quality. This invention adjusts the frequency, output power and wavelength of the pulsed laser beam so that the ratio of the total remaining load of the B-site element of the perovskite material ABX3 in the perovskite light-absorbing layer on the separated glass component to the original load of the B-site element of the perovskite material ABX3 in the untreated double-layer glass sandwich structure is more than 90%. This also means that, based on the method of this invention, a more suitable laser power for the perovskite light-absorbing layer and / or carrier transport layer can be found at different laser wavelengths and frequencies (as illustrated in the embodiments and comparative examples below), so as to achieve the separation of the double-layer glass sandwich structure without damaging the B-site element of the perovskite material ABX3 in the perovskite light-absorbing layer / transport layer. Furthermore, in addition to considering the B-site elements of the perovskite material ABX3, the pulsed laser beam parameters (i.e., frequency, output power, and wavelength) can be adjusted to further target the metal elements in the electron transport layer. This ensures that the ratio of the total residual load of the B-site elements (such as lead) of the perovskite material ABX3 on the separated glass assembly to the original load of the B-site elements of the perovskite material ABX3 in the untreated double-glass sandwich structure, and the ratio of the total residual load of the metal elements (such as indium) in the electron transport layer on the separated glass assembly to the original load of the metal elements in the electron transport layer in the untreated double-glass sandwich structure, both simultaneously meet the preset requirements.

[0026] (4) This invention uses only laser etching to separate the perovskite solar cell glass panel assembly. Combined with common acid leaching treatment, it can be directly recycled, facilitating extraction and reuse. Simultaneously, this process does not damage the glass assembly, enabling the whole-panel recycling and reuse, greatly improving the economic efficiency of recycling. In particular, after laser etching, more than 99% of the valuable elements such as lead and tin in the perovskite layer are retained in the disassembled solar panel (i.e., as adhering substances to the two completely separated glass panels). Combined with subsequent acid leaching treatment, a high recovery rate can be ensured.

[0027] In summary, this invention effectively recovers valuable elements such as lead and tin from photovoltaic modules; simultaneously, the solar photovoltaic glass panels do not need to be broken, and the intact glass panels can be recycled and reused in stages. Furthermore, the method of this invention does not require high-temperature pyrolysis of the entire perovskite solar panel, significantly reducing processing energy consumption, and avoids the large amount of organic waste liquid generated by organic solvent leaching, effectively mitigating pollution problems. This invention solves key technical challenges in the recycling of waste perovskite solar cell modules through the synergistic effect of laser processing and wet leaching, offering advantages such as simple operation, high recycling efficiency, and environmental friendliness, providing important technical support for the sustainable development of perovskite solar cells. Attached Figure Description

[0028] Figure 1 This is a process flow diagram of the present invention.

[0029] Figure 2 This is a schematic diagram of the laser etching process (the "perovskite light-absorbing layer / transport layer" in the diagram represents the stacked structure of the perovskite light-absorbing layer, hole transport layer, and electron transport layer. If the perovskite solar cell is a standard device, then from top to bottom, they are the hole transport layer, perovskite light-absorbing layer, and electron transport layer; if the perovskite solar cell is a reverse device, then from top to bottom, they are the electron transport layer, perovskite light-absorbing layer, and hole transport layer. Since their overall thickness is generally around 1 μm, or even at the nm level, which is much lower than the thickness of the encapsulation film layer, they are considered as a single structure; taking the perovskite solar cell device tested in the following embodiments as an example, electron microscopy characterization shows that the total thickness of the hole transport layer, perovskite light-absorbing layer, and electron transport layer is only 0.95 μm, which is much lower than the 470 μm thickness of the encapsulation film layer; the laser is incident from the glass side without the encapsulation film layer).

[0030] Figure 3 Transient thermal simulation diagrams of laser-etched functional layers at different power levels (the values ​​of the color labels in the diagram represent temperature values ​​in Kelvin K).

[0031] Figure 4The image shows a comparison of the UV-vis transmission spectra of a bare glass sample (i.e., a sample without a perovskite light-absorbing layer / transmission layer) obtained after acid solution extraction in Example 1 and a glass sample with a perovskite light-absorbing layer / transmission layer (i.e., a sample containing a perovskite light-absorbing layer / transmission layer) selected after physical separation.

[0032] Figure 5 This is a schematic diagram of three laser scanning methods.

[0033] Figure 6 The XRD patterns of a glass sample with a perovskite light-absorbing / transmission layer selected after physical separation are compared with those of the glass sample with a perovskite light-absorbing / transmission layer obtained by laser etching and acid leaching in Example 1.

[0034] Figure 7 The image shows a comparison of the scanning electron microscope (SEM-EDS) images of a glass sample with a perovskite light-absorbing / transmission layer selected after physical separation and the glass sample with a perovskite light-absorbing / transmission layer obtained by laser etching and acid leaching in Example 1.

[0035] Figure 8 These are physical images of the products processed at each stage of the method of the present invention; wherein, Figure 8 (a) shows the experimental sample of a double-layered glass sandwich structure that was tightly bonded before laser etching. Figure 8 (b) shows two completely separated glass components after laser etching. Detailed Implementation

[0036] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.

[0037] In general, referring to Figure 1 The present invention discloses a method for separating and recycling waste perovskite solar cell modules. This method combines mechanical dismantling, laser etching, and acid solution leaching to achieve efficient separation of the perovskite layer and recovery of key valuable components. Specifically, it includes the following steps: (1) Mechanical disassembly: The junction box and frame of the discarded perovskite solar cell module were removed to simplify the module structure and facilitate subsequent processing. The mechanically disassembled sample was a tightly bonded double-layer glass sandwich structure with an overall length of 635 mm and a width of 450 mm. In subsequent examples and comparative examples, to facilitate small-scale experiments, the large double-layer glass sandwich structure was first cut into small pieces of 5 cm × 5 cm, such as... Figure 8As shown in (a) above. Of course, other sizes, especially larger sizes, can also be used in addition to the 5 cm × 5 cm size.

[0038] After disassembly, the sample, after removing the junction box and frame, consists of the following layers from top to bottom: glass, perovskite light-absorbing / transporting layer, encapsulating film layer, and glass again. The perovskite light-absorbing / transporting layer represents a stacked structure of the perovskite light-absorbing layer, hole transport layer, and electron transport layer. If the perovskite solar cell is a functional device, the layers from top to bottom are the hole transport layer (e.g., spiro-OMeTAD, PTAA, NiO). x The structure consists of a perovskite light-absorbing layer (ABX3, where A = Cs, MA, FA, etc.; B = Pb, Sn, Ge, etc.; X = Cl, Br, I, etc.) and an electron transport layer (TiO2, SnO2, etc.). If the perovskite solar cell is an inverting device, then from top to bottom, they are the electron transport layer, the perovskite light-absorbing layer, and the hole transport layer.

[0039] (2) Laser processing: A laser of a specific wavelength (one of 355 nm, 532 nm, and 1064 nm) is directed perpendicularly to the glass and penetrates the glass layer, focusing on the perovskite layer. Energy deposition causes a chemical change in the material containing the perovskite layer, causing it to lose its adhesive properties, resulting in two completely separated glass components (the glass plates are intact and undamaged), exposing the internal sandwich layer, such as... Figure 8 As shown in (b) in the figure, this allows for the separation of the double glass layers and the exposure of the perovskite light-absorbing / transmitting layer.

[0040] (3) Acid solution leaching: The glass slides that expose key components are recovered while the complete photovoltaic glass panel is retained.

[0041] This invention applies laser etching technology to the recycling of waste perovskite solar cells. In waste perovskite solar cell modules, the perovskite layer is sandwiched between two pieces of glass and tightly connected by an encapsulating film, making efficient separation difficult using traditional methods. Figure 2 As shown, this invention utilizes laser focusing technology and the high light transmittance of glass to allow laser light to pass through the glass layer. Most of the laser energy is deposited on the perovskite light-absorbing / transmission layer, inducing a change in the properties of the perovskite light-absorbing and transmission layers (as shown in reactions 1, 2, and 3, which take FAPbI3 as the perovskite light-absorbing layer and SnO2 as the electron transport layer as examples), generating elemental lead and elemental tin, significantly reducing their adhesion to the glass and encapsulation film, thereby achieving efficient separation.

[0042] (1) (2) (3) The heat flux density generated by the laser follows a normal Gaussian distribution, expressed as:

[0043] Where Q is the heat flux density at any point within the laser spot, η is the laser utilization rate, P is the laser power, r is the laser spot radius, and R is the distance from any point to the laser center.

[0044] A moving laser source was focused onto the perovskite absorbing / transmitting layer to obtain simulation results of the temperature at the laser's point of impact. The laser power was 20 W, the laser-to-heat conversion efficiency was 80%, the laser velocity was 1 m / s, and the spot diameter was 5 × 10⁻⁶. -4 m. The laser's point of application is (x0, y0), and the distance from any point (x, y) on the surface of the perovskite absorbing / transmitting layer to the laser's center point is R, where... Simulation experiments were conducted using Comsol software to study the direct application of laser light to the surface of functional layers (hole transport layer, perovskite light-absorbing layer, and / or electron transport layer). The results showed that at a laser power of 5 W, the local maximum temperature reached 335 K. Figure 3 As shown in (a), the laser etching effect on the functional layer is not significant. This is precisely because the temperature rise corresponding to laser processing is very limited. Therefore, no volatile pollutants are generated when processing perovskite solar cell modules, effectively controlling the generation of smoke and odors and reducing environmental hazards. However, when the laser power is 20 W, as... Figure 3 As shown in (b), the local maximum temperature reached 480 K, and the functional layer showed no obvious damage. When the laser power reached 50 W, the local maximum temperature reached 700 K, and the functional layer showed some ablation, as shown in (b). Figure 3 As shown in (c); when the laser power reaches 100 W, the local maximum temperature reaches 700 K, at which point the functional layer exhibits relatively obvious ablation phenomena, such as... Figure 3 As shown in (d) in the diagram. Figure 3 (c) and Figure 3 As shown in (d), the high temperature generated by high-power lasers can cause serious damage to the functional layer, which is not conducive to the recycling of valuable metal components in waste perovskite solar cells.

[0045] Furthermore, the scanning methods of the present invention include unidirectional scanning, bidirectional filling, and annular filling. Figure 5 This ensures that the perovskite light-absorbing layer undergoes a chemical change under laser irradiation without vaporizing, thus avoiding the volatilization loss of lead and indium.

[0046] In the acid leaching step, exposed lead and indium elements are efficiently leached using a nitric acid solution to recover the metal solution while preserving the intact glass plate. This method not only boasts high recovery efficiency but also avoids the material loss and environmental pollution problems caused by high-temperature processing in traditional methods.

[0047] This invention solves a key technical problem in the recycling of waste perovskite solar cell modules through the synergistic effect of laser processing and wet leaching. It has the advantages of simple operation, high recycling efficiency and environmental friendliness, and provides important technical support for the sustainable development of perovskite solar cells.

[0048] The following are specific examples: Example 1: The lead loading is 0.80 ± 0.08 g / m³. 2 The indium loading was 1.12 ± 0.11 g / m³. 2 After removing the junction box and frame from the discarded perovskite components, the corresponding sample was obtained. The sample, from top to bottom, includes glass, SnO2, FAPbI3 perovskite, and NiO. x Indium oxide, copper-tin solder strip, polyolefin elastomer (POE) sealant, and glass. Laser etching was performed using a YDFLP-20-LP-S laser instrument (average output power 16 W, wavelength 1064 nm, frequency 50 kHz, focal length approximately 2.9 mm) in a unidirectional filling manner. The laser was directed perpendicularly to the glass (e.g., Figure 2 As shown, the laser is incident from the side of the glass without the encapsulating film layer and focused on the location of the perovskite absorbing / transmitting layer (by moving the sample up and down to focus the laser on the perovskite absorbing / transmitting layer; the same applies below). The scanning speed is 1 m / s, causing the perovskite absorbing / transmitting layer to undergo a chemical change and lose its adhesive ability, thereby achieving the separation of the double-layered glass. The total residual lead loading on the two separated glass pieces is 0.78 ± 0.11 g / m². 2 The total residual indium loading is 1.02 ± 0.03 g / m³. 2 Experimental results showed that the perovskite surface and the encapsulating adhesive surface exhibited obvious processing marks after laser processing, with a laser processing linewidth of approximately 30-40 micrometers. Subsequently, two glass slides exposed to lead and indium were immersed in a 55%-65% nitric acid solution at 200 ℃ for 2 hours, achieving a lead recovery rate of approximately 97.5% and an indium recovery rate of approximately 91.1%. Implementation Case 1 demonstrates that a laser with a frequency of 50 kHz, an output power of 16 W, a wavelength of 1064 nm, and a scanning speed of 1 m / s can achieve efficient recovery of lead and indium without damaging the glass, and effectively control the generation of fumes and odors.

[0049] Comparative Example 1: The difference between this comparative example and Example 1 is that it uses laser operating parameters of 50 kHz frequency, 20 W output power, and 1064 nm wavelength, and specifically includes the following steps: The lead loading is 0.80 ± 0.08 g / m³. 2 The indium loading was 1.12 ± 0.11 g / m³. 2 The waste perovskite components were sampled after removing the junction box and frame. The sample, from top to bottom, consisted of glass, SnO2, FAPbI3 perovskite, and NiO. x The materials used were indium oxide, copper-tin solder, polyolefin elastomer (POE) sealant, and glass. A bidirectional filling scan was performed using a 3D UV etching apparatus (average output power 20W, wavelength 1064 nm, frequency 50kHz, focal length approximately 3.0 mm; the minimum laser spot diameter of the 3D UV etching apparatus used in this invention is 10~20 μm) at a scanning speed of 1 m / s. The laser was directed perpendicularly to the glass, focusing on the perovskite light-absorbing / transmitting layer to achieve separation of the double-layered glass. The remaining lead loading was 0.14 ± 0.11 g / m³. 2 The residual indium loading was 0.08 ± 0.03 g / m³. 2 Subsequently, glass slides exposed to lead and indium were leached in a 55%-65% nitric acid solution at 200 ℃ for 2 hours, achieving recovery rates of 17.5% and 7.3%, respectively. At this point, the loss of lead and indium loading was significant, hindering recovery.

[0050] Comparative Example 2: The difference between this comparative example and Example 1 is that it uses laser operating parameters of 50 kHz frequency, 4 W output power, and 1064 nm wavelength, and specifically includes the following steps: The lead loading was 0.78 ± 0.10 g / m³. 2 The indium loading was 1.01 ± 0.10 g / m³. 2 The waste perovskite components were sampled after removing the junction box and frame. The sample, from top to bottom, consisted of glass, SnO2, FAPbI3 perovskite, and NiO. x Indium oxide, copper-tin solder, polyolefin elastomer (POE) sealant, and glass were used. Experiments were conducted using modified laser parameters, with other methods and conditions remaining unchanged. The results showed a residual lead loading of 0.37 ± 0.11 g / m³. 2 The residual indium loading was 0.22 ± 0.03 g / m³. 2After leaching with a 55%-65% nitric acid solution at 200 °C, lead recovery rates of approximately 47.0% and indium recovery rates of approximately 21.7% were achieved. Comparative Examples 1 and 2 revealed that while good separation of waste perovskite photovoltaic modules could be achieved using a laser at a frequency of 50 kHz, a wavelength of 1064 nm, and a scanning speed of 1 m / s, a large amount of key components spilled out, resulting in insufficient recovery.

[0051] Example 2: The lead loading is 0.75 ± 0.05 g / m³. 2 The indium loading is 1.10 ± 0.05 g / m³. 2 The waste perovskite components were sampled after removing the junction box and frame. The sample, from top to bottom, consisted of glass, SnO2, FAPbI3 perovskite, and NiO. x Indium oxide, copper-tin solder ribbon, polyolefin elastomer (POE) sealant, and glass. A bidirectional filling scan was performed using a 3D UV etching system (average output power 4W, wavelength 355 nm, frequency 10 kHz, focal length approximately 3.0 mm) at a scanning speed of 1 m / s. The laser was incident perpendicular to the glass direction (e.g., ...). Figure 2 As shown, the laser beam is incident from the side of the glass without the encapsulating film layer, focusing on the location of the perovskite light-absorbing / transmitting layer to separate the double-layered glass. The glass slides exposing lead and indium are then immersed in a 55%-65% nitric acid solution at 200 ℃ for 2 hours, and their elemental content is determined. The experimental results after immersion show that the residual lead loading is 0.74±0.02 g / m³. 2 The residual indium loading was 1.08 ± 0.05 g / m³. 2 After extraction with acid solution, the recovery rate of lead can reach approximately 98.7%, and the recovery rate of indium can reach approximately 98.2%. Example 2 illustrates that a laser with a frequency of 10 kHz, an output power of 4 W, and a wavelength of 355 nm can achieve efficient recovery of lead and indium elements without damaging the glass, and effectively control the generation of fumes and odors.

[0052] Comparative Example 3: The difference between this comparative example and Example 2 is that it uses laser operating parameters of 10 kHz frequency, 20 W output power, and 355 nm wavelength, and specifically includes the following steps: The lead loading was 0.77 ± 0.10 g / m³. 2 The indium loading was 1.03 ± 0.04 g / m³. 2 The waste perovskite components were sampled after removing the junction box and frame. The sample, from top to bottom, consisted of glass, SnO2, FAPbI3 perovskite, and NiO. xIndium oxide, copper-tin solder, polyolefin elastomer (POE) sealant, and glass were used. Bidirectional filling scanning was performed using a 3D UV etching system (average output power 20W, wavelength 355 nm, frequency 10 kHz, focal length approximately 3.0 mm) at a scanning speed of 1 m / s, with other methods and conditions remaining constant. Experimental results showed a lead residual loading of 0.58 ± 0.05 g / m³. 2 The residual indium loading is 0.28 ± 0.06 g / m³. 2 After extraction with acid solution, lead recovery rate of approximately 75.3% and indium recovery rate of approximately 27.2% can be achieved.

[0053] Comparative Example 4: The difference between this comparative example and Example 2 is that it uses laser operating parameters of 10 kHz frequency, 10 W output power, and 355 nm wavelength, and specifically includes the following steps: The lead loading is 0.80 ± 0.10 g / m³. 2 The indium loading was 1.08 ± 0.04 g / m³. 2 The waste perovskite components were sampled after removing the junction box and frame. The sample, from top to bottom, consisted of glass, SnO2, FAPbI3 perovskite, and NiO. x Indium oxide, copper-tin solder, polyolefin elastomer (POE) sealant, and glass were used. Bidirectional filling scanning was performed using a 3D UV etching system (average output power 10W, wavelength 355 nm, frequency 10 kHz, focal length approximately 3.0 mm) at a scanning speed of 1 m / s, with other methods and conditions remaining constant. Experimental results showed a lead residual loading of 0.70 ± 0.05 g / m³. 2 The residual indium loading is 0.29 ± 0.06 g / m³. 2 After extraction with acid solution, the recovery rate of lead was approximately 87.5%, and the recovery rate of indium was approximately 26.9%. Comparative Examples 3 and 4 showed that good separation of waste perovskite photovoltaic modules could be achieved at a frequency of 10 kHz. At low power, the lead and indium elements in the perovskite solar cells were well retained, while at high power, some losses occurred.

[0054] Comparative Example 5 This comparative example is similar to Example 1, except that the laser is incident from the back (i.e., from the side of the glass with the encapsulating film layer) and focused on the encapsulating film layer. In this case, regardless of whether the laser power is 5W or 20W, it cannot separate the double-layered glass. Because the laser is focused on the encapsulating film layer, the encapsulating film layer melts and softens under the laser's action. When the laser is removed, the melted encapsulating film material re-solidifies, actually bonding the double-layered glass even more tightly, thus failing to achieve the separation effect.

[0055] A bare glass sample obtained after acid leaching in Example 1 was characterized using UV-vis. Simultaneously, a perovskite solar cell device obtained only after mechanical disassembly was physically separated using a hammer, and a glass sample with a perovskite light-absorbing / transmitting layer was also selected and characterized using UV-vis. The results are compared as follows: Figure 4 As shown, it is easy to see that a laser with wavelengths of 355 nm, 532 nm, and 1064 nm can penetrate glass without a perovskite light-absorbing / transmission layer, but most of the light will be absorbed by glass containing a perovskite light-absorbing / transmission layer.

[0056] The glass sample with perovskite light-absorbing / transporting layer obtained after laser etching and prior acid leaching in Example 1 was characterized by XRD. Simultaneously, the perovskite solar cell device obtained after only mechanical disassembly was physically separated using a hammer, and a selected glass sample with the perovskite light-absorbing / transporting layer was also characterized by XRD. The results are as follows: Figure 6 As shown, it is easy to see that the physical appearance of the material is greatly changed after laser etching.

[0057] The glass sample with perovskite light-absorbing / transporting layer obtained after laser etching and prior acid leaching in Example 1 was characterized by SEM-EDS. Simultaneously, the perovskite solar cell device obtained after only mechanical disassembly was physically separated using a hammer, and a selected glass sample with the perovskite light-absorbing / transporting layer was also characterized by SEM-EDS. The results are as follows: Figure 7 As shown, it is easy to see that the morphology of the material changes drastically after laser etching. This can be verified by XRD patterns (…). Figure 6 ) and SEM-EDS plot ( Figure 7 The results of the change in the properties of the perovskite light-absorbing layer / transmission layer after laser treatment were verified, thus proving that the perovskite light-absorbing layer / transmission layer was separated, ensuring the separation effect.

[0058] Based on all the case studies, it is recommended to use lower power and lower frequency to achieve the separation of perovskite modules and the recovery of key components.

[0059] The above embodiments are merely examples. For instance, in addition to samples of 5 cm × 5 cm, the method of the present invention is also applicable to double-layer glass sandwich structures of other sizes, especially large-sized double-layer glass sandwich structures. Taking an uncut 0.635 m × 0.450 m sample as an example, it is also applicable, and two completely separate glass components can be obtained without the glass breaking.

[0060] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for separating and recycling perovskite solar cell modules based on laser processing, characterized in that, Includes the following steps: (1) The frame and junction box of the waste perovskite solar cell are removed by mechanical disassembly to obtain a tightly bonded double-layer glass sandwich structure; the double-layer glass sandwich structure includes two glass plates and a sandwich layer between the two glass plates; (2) Focus the laser beam fully on the hole transport layer, perovskite light-absorbing layer and / or electron transport layer in the double-layer glass sandwich structure obtained in step (1), and use a pulsed laser beam to irradiate and etch the double-layer glass sandwich structure from the vertical glass surface through a full scan, so that the area scanned by the laser focus undergoes a change in properties and loses its adhesion ability, resulting in two completely separated glass plate assemblies, thus exposing the inner sandwich layer; by adjusting the frequency, output power and wavelength of the pulsed laser beam, the total remaining load of the B site element of the perovskite material ABX3 in the perovskite light-absorbing layer on the two completely separated glass plate assemblies meets the preset requirements; the preset requirements are that the total remaining load accounts for more than 90% of the original load, and the original load is the actual load of the B site element of the perovskite material ABX3 in the double-layer glass sandwich structure obtained in step (1); (3) The two complete and separated glass components obtained in step (2) are subjected to acid solution leaching treatment so that the adhering substances on each glass are completely dissolved in the leaching solution. Then, the valuable metal elements in the leaching solution after treatment are leached and recovered. The valuable metal elements include the B-site elements of the perovskite material ABX3 in the perovskite light-absorbing layer.

2. The separation and recycling method for perovskite solar cell modules based on laser processing as described in claim 1, characterized in that, The valuable metallic element also originates from the electron transport layer; The pulsed laser beam used in step (2) also satisfies that the ratio of the total remaining load of the metal elements in the electron transport layer on the two completely separated glass components to the original load of the metal elements in the electron transport layer in the double-layer glass sandwich structure obtained in step (1) is more than 90%.

3. The separation and recycling method for perovskite solar cell modules based on laser processing as described in claim 1, characterized in that, The valuable metallic element includes at least one of lead and tin.

4. The separation and recycling method for perovskite solar cell modules based on laser processing as described in claim 3, characterized in that, The valuable metallic element is lead.

5. The separation and recycling method for perovskite solar cell modules based on laser processing as described in claim 1, characterized in that, In step (2), from the laser incident direction, the sandwich layer sequentially includes a hole transport layer, a perovskite light-absorbing layer, an electron transport layer, a conductive material layer and an encapsulation film layer, or sequentially includes an electron transport layer, a perovskite light-absorbing layer, a hole transport layer, a conductive material layer and an encapsulation film layer.

6. The separation and recycling method for perovskite solar cell modules based on laser processing as described in claim 5, characterized in that, The conductive material layer is either FTO or ITO.

7. The separation and recycling method for perovskite solar cell modules based on laser processing as described in claim 5, characterized in that, The encapsulating film layer is a type of polyolefin elastomer and polyethylene-polyvinyl acetate copolymer.

8. The separation and recycling method for perovskite solar cell modules based on laser processing as described in claim 1, characterized in that, In step (2), the frequency control range of the pulsed laser beam is 10-100KHz, the output power control range is 5-20W, and the wavelength control range is 355-1064nm; the processing speed of the pulsed laser beam is 0.5-5m / s; the full-scale scanning method includes one of unidirectional scanning, bidirectional filling, and ring filling.

9. The separation and recycling method for perovskite solar cell modules based on laser processing as described in claim 1, characterized in that, In step (2), the wavelength of the pulsed laser beam is one of 355nm, 532nm and 1064nm.

10. The separation and recycling method for perovskite solar cell modules based on laser processing as described in claim 1, characterized in that, In step (3), the acid solution is one or more of nitric acid solution, hydrochloric acid solution, acetic acid solution and sulfuric acid solution.

Citation Information

Patent Citations

  • Method for removing organic adhesive film on back surface of crystalline silicon photovoltaic module

    CN111477705A

  • Photovoltaic module recycling method based on laser etching pre-deadhesion technique and post stripping device thereof

    CN111804697A